Competency frameworks in diabetes. Issue 5 (21st February 2015) - Simmons, D.; Deakin, T.; Walsh, N.; Turner, B.; Lawrence, S.; Priest, L.; George, S.; Vanterpool, G.; McArdle, J.; Rylance, A.; Terry, G.; Little, P.
Abstract: The quality, skills and attitudes of staff working in the healthcare system are central to multidisciplinary learning and working, and to the delivery of the quality of care patients expect. Patients want to know that the staff supporting them have the right knowledge and attitudes to work in partnership, particularly for conditions such as diabetes where 95% of all care is delivered by the person with diabetes themselves. With the current changes in the NHS structures in England, and the potential for greater variation in the types of 'qualified provider', along with the recent scandal at Mid‐Staffordshire Hospital, staff need to be shown to be competent and named/accredited or recognized as such. This will help to restore faith in an increasingly devolved delivery structure. The education and validation of competency needs to be consistently delivered and assured to ensure standards are maintained for different roles and disciplines across each UK nation. Diabetes UK recommends that all NHS organizations prioritize healthcare professional education, training and competency through the implementation of a National Diabetes Competency Framework and the phased approach to delivery to address this need.